Informal work and official employment statistics: What's missing? - Anat Bracha; Mary A. Burke (Federal Reserve Bank of Boston, 2023)
Using eight consecutive waves of the Survey of Informal Work Participation (SIWP) spanning 2015 through 2022, we investigate informal "gig" work participation in the United States-broadly defined to include online and offline activities-and its implications for the measurement of employment. Our results suggest that employment rates among US household heads were consistently understated in the Current Population Survey (CPS). Under conservative estimates, we find that the employment-to-population ratio would have been 0.25 to 1.1 percentage points higher over the 2015-2022 period and as much as 5.1 percentage points higher under more generous estimates. Along the intensive margin, we find evidence that a significant number of informal work hours are missing from official employment surveys, partly because employed individuals do not fully report their informal hours. Comparing informal workers who are classified as employed by the CPS with those who are arguably misclassified as nonemployed, we find that the latter are, on average, older, less educated, and less likely to cite income as a motivation for gig work, and an elevated share are disabled. The data also indicate that certain types of income-earning activities, such as renting and selling, are less likely to be perceived as "work." These results suggest ways to improve official surveys to better capture those employed in gig work and obtain a fuller picture of the labor market.
Keywords: J21; J22; J46; J48; E26; 330; Gig work; informal work; labor market; Current Population Survey; employment